1988
DOI: 10.1128/jcm.26.1.149-150.1988
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of the ac variant in K88-positive Escherichia coli isolates from swine

Abstract: Monoclonal antibodies to K88ac and K88ab were used in enzyme-linked immunosorbent assays on Escherichia coli cultures known to produce K88 pili. A total of 415 K88-positive E. coli isolates from nine states were all found to be the K88ac variant. The cultures tested were isolated during the years 1976 to 1985.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Three antigenic variants of F4 have been described: F4ab, F4ac and F4ad (Guinée & Jansen 1979). Nevertheless, F4ac is the only variant that has been identified in the US (Westerman et al . 1988), and the F4ac variant is dominating in Spain (González et al .…”
Section: Introductionmentioning
confidence: 99%
“…Three antigenic variants of F4 have been described: F4ab, F4ac and F4ad (Guinée & Jansen 1979). Nevertheless, F4ac is the only variant that has been identified in the US (Westerman et al . 1988), and the F4ac variant is dominating in Spain (González et al .…”
Section: Introductionmentioning
confidence: 99%
“…The variant F4ac predominates in the US (Westerman et al . ), in Central Europe (Alexa et al . ; Holoda et al .…”
Section: Introductionmentioning
confidence: 99%
“…Strains of ETEC possessing the K88ac variant among those expressing the ab, ac or ad K88 ¢mbrial variants are dominant in piglets older than one week [15]. Westerman et al [15] reported that the K88ac variant is the most common, if not the only, variant of K88 adhesin found in pathogenic E. coli isolates from the major pork-producing region of the US.…”
Section: Introductionmentioning
confidence: 99%
“…Strains of ETEC possessing the K88ac variant among those expressing the ab, ac or ad K88 ¢mbrial variants are dominant in piglets older than one week [15]. Westerman et al [15] reported that the K88ac variant is the most common, if not the only, variant of K88 adhesin found in pathogenic E. coli isolates from the major pork-producing region of the US. Most of the studies have been concerned with the characterization of receptors of K88ab ¢mbriae [6,7,8,12,14] and K88ac ¢mbriae receptors on intestinal brush border cells [13,16,17].…”
Section: Introductionmentioning
confidence: 99%